Height, Health, and Inequality: The Distribution of Adult Heights in India - Deaton, Angus (American Economic Review, 2008)
This paper explores the relationship between adult heights and the distribution of income across populations of individuals. There is a long literature that examines the relationship between mean adult heights and living standards. If adult height is set by the balance between food intake and charges to disease in early childhood, it is informative about economic and epidemiological conditions in childhood. Because taller populations are better-off, more productive, and live longer, the relationship between childhood conditions and adult height has become an important focus in the study of the relationship between health and wealth. Here I follow one of the tributaries of this main stream. A relationship between income and height at the individual level has implications for the effects of income inequality on the distribution of heights. These relationships parallel, but are somewhat more concrete than, the various relationships between income inequality and health that have been debated in the economic and epidemiological literatures, Richard G. Wilkinson (1996), Angus Deaton (2003).